Vulnerable earth : The literature of climate crisis - Nayar, Pramod K. (New Delhi : Cambridge University Press, 2024)
Vulnerable Earth is a study of the literature of climate crisis. Building on the assumption that the crisis is planetary in scope even if differential and unequal in effects, it examines literary fiction, graphic novels, memoirs about toxic wastes and neo-slavery narratives, mostly from the contemporary decades, but touching upon select antecedents as well, and from all over the world. The study covers texts that fictionalize a 'hydrocrisis', those that are concerned with species extinction and experimental solutions such as rewilding, fiction and memoirs that are interested in exploring the conversations between and across species in multispecies encounters and, finally, texts that show the linkage between social justice and environmental justice. Focusing on aesthetics, narrative modes and constructions of damaged, wasted and at-risk worlds, this book shows how the literature of climate crisis foregrounds a feature that humans and nonhumans, the living and the non-living share, differentially, with the planet: vulnerability.
Keywords: Environmental History